Enhanced machining features and multi-objective optimization of CNT mixed-EDM process for processing 316L steel - Danish, M. (Springer Science and Business Media Deutschland GmbH, 2022)
There is a high roughness and tool wear rate (TER), and a minimal material erosion rate (MER) when 316L steel is machined through conventional or conductive powder mixed electro-discharge (EDM) processes. Since the required machining outputs are primarily dependent on process parameters due to their fluctuating nature during the operation, a thorough study is required. This research intends to investigate the effects of EDM process parameters on the machining outputs. The carbon nanotubes (CNT) are added to the working dielectric to achieve a high MER with a low TER and surface roughness (SR). The machined surfaceâs morphology and composition are validated using scanning electron microscope (SEM) and electron dispersive X-ray (EDX). Taguchiâs design has been employed to conduct the EDM process parametric optimization obtaining the smallest TER and SR of 0.34Â mg/min and 1.55Â Âµm, respectively. The greatest MER of 39.76Â mg/min, which is considered for the machining efficacy, is obtained. The most relevant factor for MER, TER, and SR is current intensity, followed by CNT quantity, according to analysis of variance (ANOVA). The estimated errors of theÂ predicted solution sets using theÂ multi-objective ant lion optimizer (MOALO) are less than 10, which confirm a high prediction of them. Findings of this research will result in an effective manufacturing process for fabricating the devices made of 316L steel for biomedical and oil and gas applications. Â© 2022, The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature.